Candidate Molecular Compounds as Potential Indicators for Meibomian Gland Dysfunction - Asiedu, Kofi (Frontiers in Medicine, 2022)
Meibomian gland dysfunction (MGD) is the leading cause of dry eye disease throughout the world. Studies have shown that several molecules in meibum, including but not limited to interleukins, amino acids, cadherins, eicosanoids, carbohydrates, and proteins, are altered in meibomian gland dysfunction compared with healthy normal controls. Some of these molecules such as antileukoproteinase, phospholipase A2, and lactoperoxidase also show differences in concentrations in tears between meibomian gland dysfunction and dry eye disease, further boosting hopes as candidate biomarkers. MGD is a complex condition, making it difficult to distinguish patients using single biomarkers. Therefore, multiple biomarkers forming a multiplex panel may be required. This review aims to describe molecules comprising lipids, proteins, and carbohydrates with the potential of serving various capacities as monitoring, predictive, diagnostic, and risk biomarkers for meibomian gland dysfunction.